2021
DOI: 10.3390/ijerph182111282
|View full text |Cite
|
Sign up to set email alerts
|

Ostracism, Psychological Capital, Perceived Social Support and Depression among Economically Disadvantaged Youths: A Moderated Mediation Model

Abstract: Mental health promotion of economically disadvantaged youths is a popular issue in current China. Economically disadvantaged youths are at greater risk of depression. Ostracism may be an important predictor of depression for them. However, no consensus has been reached on the underlying mechanism between ostracism and depression. A total of 1207 economically disadvantaged youths were recruited from six universities in China. These youths were asked to complete questionnaires measuring depression, ostracism, ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…The study showed that psychological capital was positively correlated with perceived social support, and negatively correlated with perceived employment pressure and depressive symptoms, while perceived social support was negatively correlated with depressive symptoms ( 10 ); in the relationship between the two, perceived social support acted as a mediator, which showed that perceived social support provides more paths consistent with previous studies ( 10 , 29 ). In addition, the study revealed that perceived social support partially mediated the effect of depressive symptoms alleviated by psychological capital.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The study showed that psychological capital was positively correlated with perceived social support, and negatively correlated with perceived employment pressure and depressive symptoms, while perceived social support was negatively correlated with depressive symptoms ( 10 ); in the relationship between the two, perceived social support acted as a mediator, which showed that perceived social support provides more paths consistent with previous studies ( 10 , 29 ). In addition, the study revealed that perceived social support partially mediated the effect of depressive symptoms alleviated by psychological capital.…”
Section: Discussionsupporting
confidence: 76%
“…Psychological capital can predict depression ( 10 ). The broaden-and-built theory denotes that psychological resources (e.g., psychological capital) can help individuals form positive emotion regulation strategies against negative emotions ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, through the heterotrait–monotrait ratio (HTMT) [ 59 ], the discriminant validity was tested. The HTMT value should be ≤0.90 to be deemed significant.…”
Section: Resultsmentioning
confidence: 99%
“…According to this model, ostracized individuals feel pain, experience negative emotions, and perceive the experience as a threat to their basic human needs (e.g., meaningful existence or self-esteem). Individuals who cannot respond to the reactions due to fear are faced with adverse outcomes such as depression and hopelessness (Williams, 2009;Yu et al, 2021). Against this backdrop, ostracism has been defined as "social death" (Williams et al, 2000).…”
Section: Ostracism Cyberostracism and Knowledge Sharingmentioning
confidence: 99%